Disrupting narratives of isolation: the production and circulation of ideas in Colombia about Latin America’s progress, 1870–1900 - Campuzano-Hoyos, Jairo (Trashumante. Revista Americana de Historia Social, 2021)
Abstract: Colombians were not isolated during the last third of the nineteenth century. Transportation difficulties that slowed the movement of people and goods—a particularly challenging issue in the Andean region—proved less of a hindrance for the movement of ideas. Many intellectuals, seeking knowledge about Latin America’s latest progress, worked diligently to promote the spread and understanding of global ideas among fellow Colombians. They looked to learn from republics in the region, with whom they also developed mutually beneficial intellectual and material relationships. Colombian intellectuals, many of whom played a decisive role in diplomatic postings abroad, facilitated this circulation of ideas within Colombia.
Keywords: Business history in Latin America; circulación de ideas; diplomáticos; historia transnacional; intelectuales; redes